La imagen de los judíos en los sermones de Bartomeu Catany, O.F.M. (c. 1380-1462) - Catalán Casanova, Oriol (Hispania sacra, 2017)
This article widens the traditional political analysis of the sermons by the Franciscan friar Bartomeu Catany (c. 1380-1462) by showing the image of the Jews that the sermons transmitted, the sources used, the relation of these sermons with the anti-Jewish literature in 15th century, and their role in the evolution of hatred in the context of xvth-century Majorcan society and the persecution and expulsion of the Jews from the Hispanic Kingdoms.